Information in action : - Davies, Lynda (MacMillan, 1991)
This book focuses on this crucial area of managerial activity and describes an approach for talking the core problem of information management - the approach being soft systems methodology. The concepts, methods and techniques which form systems methodology are discussed in detail, in addition, the problems and pitfalls of applying the approach in real-life situations are examined